Indian Journal of Nematology (Indian Journal of Nematology, 2024)
EDITORIAL BOARDEditor-in-Chief : DR. PANKAJ ,Editor : DR. T.K. DUTIAMEMBERSPROF. QAMARMAJEED, Sokoto, NigeriaPROF. H.S. GAUR, MeerutPROF. IRSHAD MAHMOOD, AligarhDR. KEITH G. DAVIES, UKDR. RICHARD SIKORA, GermanyDR. BYRON ADAMS, USADR. R.K. KAUL, JodhpurDR. SJ EAPEN, CalicutDR.M. NAGESH, ShimlaDR. S.S. HUSAINI, BangaloreDR. ANJU VERMA, USADR. S.B. SHARMA, AustraliaDR. ALY KHAN, PakistanDR. A.U. SIDDIQUI, UdaipurDR. K.K. KAUSHAL, New DelhiDR. A.H. WANI, JammuDR. B.A. PATEL, AnandDR. R.K. WALIA, New Delhi DR. N.K DHILLON, Ludhiana